Answerable for our beliefs reflections on theology and contemporary culture offered to Terrence Merrigan - Mey, Peter de 1966-; Struys, Kristof 1972-; Coman, Viorel ca. 20./21. Jh (Peeters, 2022)
With this Festschrift colleagues and friends honor Terrence Merrigan on the occasion of his retirement from the Faculty of Theology and Religious Studies, KU Leuven. The thirty-two contributions in this volume all show the exceptional quality of his research in different domains of theological study. Since the theology of John Henry Newman has inspired Terrence Merrigan throughout his entire career, the volume opens with a number of outstanding studies on various aspects of Newman's theology: his interaction with high church Anglicanism, his understanding of conscience, the theology of purgatory, but also the neglect of liturgical spirituality in Newman's theology. The contributions in the second part are devoted to the fields of Christology and Trinity, which comprise Merrigan's favorite theological disciplines. The contributions are situated on the intersection of contemporary Christology and its soteriological impact within a pluralistic and secularized context. The third part deals with the theology of interreligious dialogue, with special focus on the teachings of the Second Vatican Council, Jacques Dupuis's theology of religions, comparative theology, Jewish and Christian approaches to interreligious dialogue, and the phenomenon of double religious belonging. The fourth part explores the challenging relationship between faith and culture in an attempt to bridge the Christian tradition with the contemporary world. The present volume makes a distinguished and original contribution to these four important fields of theological research.
Keywords: Newman, John Henry -- Heiliger -- 1801-1890; Christologie; Trinitätslehre; Ekklesiologie; Interreligiöser Dialog; Jesus Christ / Person and offices; Bible / New Testament / Criticism, interpretation, etc; Theology / 21st century; Christianity and other religions; Festschrift